Filsafat Pendidikan Islam: Pendidikan Multikultural - Lathifah Abdiyah (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Indonesia is a nation consisting of various cultures, tribes, groups, religions, ethnicities, races, social classes, and so on. Even though it is built on diversity, every nation has a background in improving multicultural education. This background is at least a reason and gives a new color to how multicultural education is developed and implemented. Multicultural education recognizes the ethnic and cultural diversity of the people of a nation. Multicultural education is a form of effort in a harmonious relationship, namely educational activities with the aim of growing and developing the wisdom of understanding, attitudes, awareness, and behavior of students towards cultural, community, and religious diversity. The method in this study uses library research methods (library). This paper aims to explain the nature of multicultural education, how the principles, objectives, functions, and perspectives of multicultural education are related, how multicultural education is in the philosophy of Islamic education, and how multicultural education is in Indonesia. Indonesia adalah bangsa yang terdiri dari aneka budaya, suku, golongan, agama, etnis, ras, kelas sosial, dan sebagainya. Meski terbangun atas bermacam keragaman, setiap bangsa memiliki latar belakang dalam meningkatkan pendidikan multikultural. Latar belakang ini setidaknya menjadi alasan serta memberi warna baru bagaimana pendidikan multikultural dikembangkan serta diterapkan. Pendidikan multikultural mengakui adanya keberagaman etnik dan budaya masyarakat suatu bangsa. Pendidikan multikultural merupakan suatu bentuk upaya dalam mewujudkan hubungan yang harmonis, yaitu kegiatan edukasi dengan maksud menumbuh kembangkan kearifan pemahaman, sikap, kesadaran, dan perilaku peserta didik terhadap keaneka ragaman budaya, masyarakat, dan agama. Metode dalam penelitian ini menggunakan metode library research (pustaka). Makalah ini bertujuan untuk memaparkan terkait bagaimana hakikat pendidikan multikultural, bagaimana prinsip, tujuan, fungsi, dan perspektif pendidikan multikultural, bagaimana pendidikan multikultural dalam filsafat pendidikan Islam, dan bagaimana pendidikan multikultural di Indonesia.